Provenance differences and factors influencing transpiration of Cunninghamia lanceolata in a common garden experiment - Xu, Tingyu; Niu, Xiang; Wang, Bing (Frontiers in Plant Science, 2025)
Tree transpiration is a key component of forest evapotranspiration, and sap flow monitoring is the primary way to study tree canopy transpiration and water consumption. However, provenance differences in transpiration and the unique responses to environmental factors are not well understood. We measured the sap flow and calculated the canopy evapotranspiration (Ec) of 15 Chinese fir provenances from five provinces in a common garden and monitored soil moisture and meteorological variables between September 2020 and September 2022. Mean daily Ec of the provenances from Guangxi (GX), Sichuan (SC), Anhui (AH), Yunan (YN), and Zhejiang (ZJ) were 1.31 ± 0.99 g·d−1, 1.59 ± 1.18 g·d−1, 1.62 ± 1.43 g·d−1, 1.41 ± 1.01 g·d−1, and 1.48 ± 1.13 g·d−1 during the study period, respectively. The mean daily Ec of Guangxi, Sichuan, Anhui, Yunan, and Zhejiang provenances exhibited significant differences (p <0.01). Overall, the Ec of these provenances was high from June to August. Soil moisture had different effects on the Ec of the provenances. The provenances from Zhejiang, Sichuan, and Anhui showed higher Ec values when REW <0.4 than REW≥0.4 conditions, but the Ec of Guangxi and Yunnan provenances showed no significant differences under the two conditions. When the soil was relatively moist, Ec of the provenances was mainly influenced by Rs and VPD. When the soil was relatively dry, the main influencing factors were the Ta and VPD. Overall, our findings revealed different provenance-specific responses of Ec to biophysical factors, providing valuable insights for the selection of superior provenances of Chinese fir from the perspective of water use in the context of a changing climate.